New Synthetic Route of Ultrapure Alkylammonium Iodides for Perovskite Thin Films of Superior Optoelectronic Properties. Issue 10 (9th September 2020) - Dasgupta, Shyantan; Misztal, Kasjan; Fuentes Pineda, Rosinda; Mróz, Wojciech; Pawlaczyk, Łukasz; Serafińczuk, Jarosław; Barker, Alex J.; Ahmad, Taimoor; Herman, Artur P.; Sahayaraj, Sylvester; Kudrawiec, Robert; Petrozza, Annamaria; et al.
Abstract : In the past decade, metal halide perovskites grew from a mere scientific sensation to a tangible photovoltaic technology, being on the brink of commercial entrance. Certified efficiency value reported for these devices exceeded 25%. However, there still remains a large scope for further advancement, particularly in better understanding of the formation process of polycrystalline thin films of these materials. Insight into the interplay between colloidal precursor solution and nucleation of perovskite crystallites is highly desirable to obtain well‐controlled crystallization process, essential for reproducible manufacturing at large scale. Herein, a novel synthetic route of methylammonium iodide (CH3 NH3 I, MAI) is reported, which produces ultrapure material with a cheap and simple method. MAI prepared this way obtains better control over the perovskite precursor colloidal solution. Furthermore, MAPbI3 perovskite layers processed from solutions are formulated with different MAI powders, and these films are applied into a simple planar heterojunction solar cell stack. Through photovoltaic performance characterization and multiple spectroscopic measurements, superior optoelectronic properties of samples made with an optimized solution are demonstrated. The influence of a precursor solution and its colloidal distribution on the final film properties is reported. The reported synthetic protocol is also applicable to other alkylammonium iodides. Abstract : Novel synthetic route of producing ultrapure alkylammonium iodide is demonstrated. Methylammonium iodide prepared this way allows obtaining better control over the perovskite precursor colloidal solution. Furthermore, MAPbI3 perovskite layers fabricate from the optimized precursor formulation exhibit superior optoelectronic properties, as demonstrated with a range of crystallographic, electrical, and spectroscopic techniques.